2016
DOI: 10.1590/1982-0194201600055
|View full text |Cite
|
Sign up to set email alerts
|

Indução da dor pelo quimioterápico docetaxel em mulheres com câncer de mama

Abstract: Resumo Objetivo Descrever a frequência, características, localização, intensidade da dor em pacientes com câncer de mama em uso do quimioterápico Docetaxel. Métodos Estudo longitudinal realizado com 17 mulheres com câncer de mama em tratamento com Docetaxel. As pacientes foram avaliadas durante três ciclos da quimioterapia quanto à dor, utilizando-se os instrumentos Questionário McGill de Dor (Br-MPQ) e Brief Pain Inventory (BPI). Utilizou-se a correlação de Spearman e o teste de Mann-Whitney. Resultados … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
1
0
0
2
Order By: Relevance
“…These collateral effects produced by the treatments leave lasting sequelae, compromising several biological systems (Battaglini, Bottaro, Campbell, Novaes, & Simão, 2004), affecting in general the quality of life of these patients. Like the results of the present study, Neris, Magnabosco, Amaral, Ribeiro and dos Anjos, (2016), who accompanied patients during chemotherapy, also pointed out an increase in the presence and intensity of pain during the chemotherapy treatment. Most of these patients suffer from post-treatment symptoms such as nausea, vomiting, insomnia, pain, loss of appetite and fatigue (Adamsen et al, 2009), as well as those reported by the present study.…”
Section: Discussionsupporting
confidence: 87%
“…These collateral effects produced by the treatments leave lasting sequelae, compromising several biological systems (Battaglini, Bottaro, Campbell, Novaes, & Simão, 2004), affecting in general the quality of life of these patients. Like the results of the present study, Neris, Magnabosco, Amaral, Ribeiro and dos Anjos, (2016), who accompanied patients during chemotherapy, also pointed out an increase in the presence and intensity of pain during the chemotherapy treatment. Most of these patients suffer from post-treatment symptoms such as nausea, vomiting, insomnia, pain, loss of appetite and fatigue (Adamsen et al, 2009), as well as those reported by the present study.…”
Section: Discussionsupporting
confidence: 87%
“…A avaliação da dor em mulheres com câncer de mama pós tratamento encontrou resultados semelhantes nos estudos de Anjos (2016), onde aparecem os seguintes aspectos mais afetados pela dor: humor, trabalho normal e sono.…”
Section: Sobre O Acompanhamento Pós Tratamentounclassified
“…Dessa forma, o rompimento do equilíbrio celular modifica função e estrutura da célula, resultando na apoptose. Este fármaco é considerado de primeira opção para tratamento quimioterápico de câncer de próstata (NERIS et al, 2016).…”
Section: Fonte: Os Autoresunclassified